Early fresh‐frozen plasma transfusion decreases the risk of retinopathy of prematurity. Issue 4 (9th October 2013) - Dani, Carlo; Poggi, Chiara; Bresci, Cecilia; Corsini, Iuri; Frosini, Saverio; Pratesi, Simone
<x xml:space="preserve">Abstract</x> Background Insulin‐like growth factor 1 (IGF‐1) and IGF‐binding protein‐3 (IGFBP‐3) play a main role in the pathogenesis of retinopathy of prematurity (ROP). Fresh‐frozen plasma (FFP) from adult donors may be an actual source of IGF‐1 and IGFBP‐3 because it contains higher concentrations. The objective was to evaluate whether FFP transfusions can decrease the occurrence of ROP in a cohort of preterm infants. Study Design and Methods We retrospectively analyzed data from 218 infants with gestational age of less than 29 weeks who either received FFP or did not and correlated this procedure to the development of any grade of ROP. Results Logistic regression analysis demonstrated that two or more transfusions of FFP was effective in decreasing the risk of development of any grade of ROP (relative risk, 0.46; 95% confidence interval, 0.23‐0.93). Other factors that affected the risk of ROP were gestational age, birthweight, antenatal steroid treatment, FiO2 of at least 0.40, mechanical ventilation, and sepsis. Conclusions We found that two or more transfusions of FFP in the first week of life decrease the risk of developing any grade of ROP in preterm infants with gestational age of less than 29 weeks.